PDIP NTB Political Communication in Building Loyalty of Cadres and Constituents in Elections - Nur Ramdhani; Rosita Anggraini (Institute of Computer Science (IOCS), 2021)
The Indonesian Democratic Party of Struggle (PDI-P) as a cadre party cannot be separated from the phenomenon of internal competition. In this case, the central actor of PDIP NTB as the leader of a cadre-based nationalist party in areas where the majority of the Muslim community is required to have a communication adaptation strategy at both the cadre and constituent levels. Although PDIP NTB experienced internal competition among cadres in the 2009-2019 election contestation, the role of the central actor of PDIP NTB was able to reduce and maintain the vote acquisition to win seats in the DPR RI Election of NTB. This study aims to see the role of central actors in building political communication to maintain the loyalty of cadres and constituents in facing the 2009-2019 DPR RI elections. Through the analysis of Political Public Relations (McNair, 2011), this article focuses on the communication role of the central actor in PDIP NTB. in maintaining the loyalty of cadres and constituents to win the legislative seats of the DPR RI in the 2009-2019 elections. This article is a qualitative research based on primary and secondary data in the form of direct interviews to four informant and a collection of official documents explaining the role of the central actor in PDIP NTB. This study argues that, the role of the central elite with the ability of political communication through the use of various internal communication channels and good information management as well as forming the loyalty of cadres and constituents is able to gain seat of DPR RI in the 2009-2019 elections.